Dynamical behaviours and fractional alphabetical-exotic solitons in a coupled nonlinear electrical transmission lattice including wave obliqueness - Fendzi-Donfack, E.; Tala-Tebue, E.; İnç, Mustafa; Kenfack-Jiotsa, A.; Nguenang, J. P.; Nana, L. (Springer, 2023)
We investigate through the ansatz and auxiliary equation methods novel types of solitary wave solutions for (2+1)-D coupled nonlinear electrical transmission lattice with wave obliqueness. While including the fractional conformable derivatives in addition to the wave obliqueness parameter, we turn the fractional circuit equation into an ordinary differential equation. Therefore, we explore some fractional alphabetic and exotic solitons, solutions of the equation governing the dynamics of the voltage wave for the studied model. With the graphical representation of the novel obtained solutions, we highlight the effects of the fractional order and the wave obliqueness parameter. From the physical parameters of the circuit and the wave obliqueness parameter we examine the stationary points.
Keywords: Auxiliary equation methods; Fractional conformable derivatives; Exotical solitons; Wave obliqueness parameters; M-shaped solitons; Phase portrait